Stiffness profiles of organic soils based on the MASW method - Jón Snorri Jóhannsson 1995- (2020)
In many civil engineering projects, knowledge of the geotechnical properties of the soil is essential. Many different methods exist to acquire these properties and they all come with their own pros and cons. One of these methods is the Multichannel Analysis of Surface Waves (MASW) which is a fairly new method where surface waves are generated to measure the shear wave velocity. MASW is both a low-cost and a non-invasive method, making it environmentally friendly. All the necessary equipment can be transported in a 1 m^3 box and the test leaves no lasting marks on the site. The MASW method is divided into three main steps: data acquisition, dispersion analysis, and inversion analysis. MASW measurements have been carried out in Iceland before and were used as references and a basis for this thesis. The main objective of this project is to expand on the current MASW knowledge in Iceland by focusing on MASW measurements solely in peat and organic soil. For this project, measurements were performed at two locations in South-West Iceland. The measurements were taken with multiple different receiver setups and number of receivers which affected the quality of the data. Data from one additional site was included which was acquired by a third party. Validation of the MASW measurements was done with multiple different CPT-V_S correlations along with CPT data from The Icelandic Road Administration (Vegagerðin). Í mörgum verkefnum tengdum byggingarverkfræði, er þekking á jarðtæknilegum eiginleikum jarðvegsins nauðsynleg. Til eru margar mismunandi aðferðir við að útvega þessa eiginleika og koma þær allar með sínum kostum og göllum. Ein af þessum aðferðum er Multichannel Analysis of Surface Waves (MASW) sem er tiltölulega ný aðferð þar sem yfirborðsbylgjur eru myndaðar til mæla skúfbylgjuhraða. MASW er bæði ódýr og fljótleg í framkvæmd, sem gerir hana einnig umhverfisvæna. Hægt er að flytja allan nauðsynlegan búnað í 1 m^3 boxi og mælingarnar valda engum varanlegum skemmdum á yfirborði staðarins. MASW aðferðinni er skipt ...